Prevalence of Atherosclerotic Cardiovascular Disease, Heart Failure, and Chronic Kidney Disease in Patients with Type 2 Diabetes Mellitus: A Primary Care Research Network-based Study - Goderis, Geert; Vaes, Bert; Mamouris, Pavlos; van Craeyveld, Eline; Mathieu, Chantal (Experimental and Clinical Endocrinology & Diabetes, 2021)
Aims This study aims to assess the prevalence of atherosclerotic cardiovascular disease (ASCVD), heart failure (HF), chronic kidney disease (CKD), and their combined presence in type 2 diabetes (T2D) patients in primary care for whom the 2019 ADA/EASD consensus update “Management of Hyperglycemia in Type 2 Diabetes” recommends GLP-1 receptor agonists (GLP-1RA) or sodium-glucose cotransporter-2 inhibitors (SGLT-I) as first-line medications after metformin.Methods Data were obtained in 2015 from Intego, a morbidity registration network of 111 general practitioners (GPs) working in 48 practices and including 123 261 registered patients.Results Of 123 261 patients, 9616 had T2D. Of these patients, 4200 (43.7%) presented with ASCVD and/or CKD and/or HF. Specifically, 3348 (34.8%) patients had ASCVD, 388 (4.0%) had heart failure, and 1402 (14.6%) had CKD. Compared to patients without any of these comorbidities, patients with at least 1 of these conditions were older (69.7 ±12.6 vs. 63.1±12.5 years), had higher LDL-C values (104.2±35.8 mg/dl vs. 97.2±37.7) and less frequently achieved the systolic blood pressure target of 140 mm Hg (53 vs. 61%) (all p<0.001). Comorbid patients also had significantly more other comorbidities, such as dementia or cancer; received more recommended medications, such as statins; and received less metformin. Most patients with HF (325; 3.4%) had ASCVD (114; 1.2%), CKD (76; 0.8%), or both (135; 1.4%). In total, 478 patients with CKD (5.0%) also had ASCVD.Conclusions At the primary care level, 44% of T2D patients suffer from ASCVD, CKD, and/or HF, and thus qualify for GLP-1RA or SGLT2-I therapy.
Keywords: ASCVD; heart failure; CKD; type 2 diabetes mellitus